Application of extended finite element method for plastic hinges and yield lines analysis - Xu, Jin (2013)
The application of extended finite element method (XFEM) formulation for nonlinear structural analyses is presented in this thesis. It aims to capture accurately the elastic response of a beam with an internal pin connection and the elasto-plastic response of a beam or a plate structure at a relatively low computational cost by utilizing the XFEM Timoshenko beam and Reissner-Mindlin plate elements.